2020
DOI: 10.1177/1359104520904120
|View full text |Cite
|
Sign up to set email alerts
|

Measuring psychological outcomes in paediatric settings: Making outcomes meaningful using client-defined perspectives

Abstract: There is a growing drive to develop and implement patient-reported outcome measures within paediatric health services, particularly for young people living with chronic health conditions; however, there is little consensus on how best to do this in meaningful ways within psychological services working alongside medical teams. This reflective commentary considers some of the challenges of collecting psychological outcome measures in paediatric services and considers alternative approaches to making outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…More standard measures, designed to be meaningful and sensitive to changes in core sign and symptom domains or co-occurring conditions and that can be compared across treatments, are necessary. 4,[276][277][278] Patient-reported outcome measures, often completed by parents or carers and teachers for children, are important, 279 but many autism interventions are psychosocial, hindering the masking of participants, parents, and teachers who are best placed to report on meaningful everyday outcomes. Placebo effects are also well known to be strong.…”
Section: Measuring Outcomesmentioning
confidence: 99%
“…More standard measures, designed to be meaningful and sensitive to changes in core sign and symptom domains or co-occurring conditions and that can be compared across treatments, are necessary. 4,[276][277][278] Patient-reported outcome measures, often completed by parents or carers and teachers for children, are important, 279 but many autism interventions are psychosocial, hindering the masking of participants, parents, and teachers who are best placed to report on meaningful everyday outcomes. Placebo effects are also well known to be strong.…”
Section: Measuring Outcomesmentioning
confidence: 99%
“…Importantly, a fully nomothetic or clinical symptomatic-based outcome measure is not suitable for this type of therapeutic intervention, as discussed in the introduction to this paper, we would not expect a change in symptomatology directly after one therapy session. I-PROMs, however, are useful as they align more with patient-perceived progress rather than measurement being centred around the clinician perceived symptomatic progress (Collins, 2019;Flannery and Jacob, 2020) but still allow for aggregation of scores. Therefore, we identified that this style of measures is particularly appropriate for measuring outcomes from single-session or drop-ins as they are commonly informative, asset-based and solution-focussed (Dryden, 2020;Kachor and Brothwell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These routinely collected Patient-Reported Outcome Measures (PROMs) have been seen to be useful in mental health settings and provide the patient with a more holistic progress measure that reduces treatment failur and enhances positive effects of the intervention (Brattland et al, 2018;Lambert and Harmon, 2018). PROMs are important as they align more with patient-perceived change and progress rather than measurement being centred around the clinician perceived symptomatic progress (Collins, 2019;Flannery and Jacob, 2020). Therefore, the use of nomothetic PROMs aims to give the patient a voice in their mental health journey, but they fail to capture individualised wants and needs in treatment and measure the person's experience of change, which may not be shown in clinical measure alone.…”
Section: Introductionmentioning
confidence: 99%
“…Simple steps like raising awareness can help people understand that they are not alone in their struggles with symptoms and, by implication, there is no shame in talking about and seeking help for them. Similarly a lot can be done to ensure that we are sensitive in our research and practice about what matters to people and their mental health and recovery beyond the sole focus on symptoms or diagnoses to what helps participants and patients achieve quality of life and well-being (Flannery & Jacob, 2020).…”
Section: Rebranding Is Insufficientmentioning
confidence: 99%